Kajian Fisiologis Penggunaan Bovine Somatotropin (bST) Pada Sapi Pra Afkir - Dzarnisa Dzarnisa; Cut Aida Fitri (Agricultural Faculty, 2009)
Studies of physiological bovine somatotropin (bST) on post lactating dairyABSTRACT. To increase of milk production nationally with used in dairy cattle business can assist to increase milk production, eighteen post lactating dairy cows in the highland Cipelang Bogor, were used to study the effect used of bovine somatotropin and lactating time. The experimental cows were assigned into a Randomized Block Design with a 3x2 factorial arrangement. The first factor was using of somatotropin (bST)with three levels (non bST injection, biweekly injection and three weekly injection). The second factor was lactating time with two levels (4th lactating time and 6 th lactating time) Parameters measured were heart rate, respiration frequency, rectal temperature, milk production efficiency, milk production, 4% FCM (fat corrected milk.), Milk composition, weigh gain, milk quality consist of protein, fat, pH. Bovine somatotropin significantly increased heart rate and respiration rate. Also bovine somatotropin injection at 4th lactating time significantly increased milk production. There were an interaction between bST dan lactating time on milk production and weight gain. Bovine somatotropin injection biweekly in cows on 4th lactating time ration increased milk production by 16-26 %, but injection in cows 6th lactating time increased milk production by 8-18 % combination with somatotropin doze 250/ml/14 days. Somatothropine supplementation was injection biweekly and three weekly did significantly affect to milk production, body temperature, heart rate, and respiration rate however in normal physiology . Bovine somatotropine can increase post lactating dairy production interval 14 days better than 21 days.